Women's preconception psychological stress and birth outcomes in a fertility clinic: the EARTH study - Mínguez-Alarcón, Lidia; Williams, Paige L.; Souter, Irene; Ford, Jennifer B.; Hauser, Russ; Chavarro, Jorge E. (Frontiers in Global Women's Health, 2024)
Background The epidemiologic literature on women's perceived stress in relation to perinatal outcomes has been inconclusive and does not consider the preconception window of exposure. Objective To evaluate whether women's preconception perceived stress is related to live birth, gestational age, and birthweight in a cohort receiving fertility treatment. Methods This observational study included women seeking fertility care at the Massachusetts General Hospital (2004–2019). During preconception, women provided information on their psychological stress using the short version of the validated Perceived Stress Scale 4 (PSS-4). We used regression models to evaluate the associations of stress with live birth (N = 768 attempting to conceive) and perinatal outcomes (N = 413 live births) while adjusting for confounders. Stratified analyses by mode of conception [natural, intrauterine insemination (IUI), and IVF (in vitro fertilization)] and selected socioeconomic factors (race, education, and income) were also conducted. Results Higher psychological stress was negatively associated with the overall probability of live birth (adjusted RR = 0.95, 95% CI: 0.92, 0.98), particularly among women conceiving using IVF. However, we found no association between women's psychological stress and gestational age and birth weight in the overall analyses and also stratified by mode of conception. Similarly, we observed no differences in women's psychological stress with any of the measured outcomes by socioeconomic factors. Discussion These results highlight the importance of considering the preconception window and mode of conception when evaluating the relationship between women's preconception stress and live birth.